A bibliometric review exploring the nexus between sustainability and food entrepreneurship - M. Ajay Adithya; R. Geetha; S. Sundar (Discover Sustainability)
Abstract Accelerating global pursuit of sustainable food systems has amplified scholarly interest in the emerging domain of sustainable food entrepreneurship, an interdisciplinary domain at the nexus of environmental sustainability, innovation, and inclusive development. While the term ‘sustainable food entrepreneurship’ remains emergent in academic discourse, it offers a useful conceptual lens to explore how entrepreneurial practices contribute to sustainability transitions in food systems. This study presents a comprehensive bibliometric review of SFE research from 2014 to 2024, synthesizing 422 peer-reviewed publications indexed in the Scopus database. Utilizing VOSviewer and Biblioshiny, the analysis maps publication trends, influential authors, institutional and international collaboration networks, and evolving thematic structures. The findings reveal a significant growth trajectory in SFE scholarship, albeit with pronounced geographic and disciplinary imbalances. Key research clusters highlight emergent areas such as agri-food innovation, circular economy models, food justice, and digital entrepreneurship. However, the study also identifies underrepresentation of Global South perspectives and a lack of integration between theoretical frameworks and empirical patterns. Anchored in the Sustainable Food Entrepreneurship Framework, the Triple Bottom Line, and Stakeholder Theory, this review interprets the intellectual landscape of SFE through a theory-informed lens. The paper offers actionable insights for researchers, practitioners, and policymakers by uncovering structural gaps, innovation hotspots, and collaborative opportunities. It advocates for a more inclusive, theory-driven, and policy-relevant research agenda aligned with the Sustainable Development Goals. This bibliometric synthesis not only contributes to academic discourse but also informs real-world strategies for building equitable and resilient food entrepreneurship ecosystems.